2017
DOI: 10.1109/te.2017.2648781
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effect of Program Visualization on Student Motivation

Abstract: An increase in student motivation is often cited as an expected effect of software visualization, but, as far as the authors are aware, no controlled experiments have yet demonstrated this. This paper therefore presents a controlled evaluation of this effect, conducted within the framework of self-determination theory. Students were tasked with removing redundant recursion in a multiple recursive algorithm. The experimental group (N=19) used the SRec program visualization system, while the control group (N=17)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 34 publications
0
15
0
3
Order By: Relevance
“…ET has historically been one of the most commonly used evaluation frameworks (Banerjee, Murthy, & Iyer, 2015;Velázquez-Iturbide et al, 2017). Even though previous studies measured the effect of engagement level on learning outcomes, their results were not consistent (Banerjee et al, 2015).…”
Section: The Role Of Engagement With Software Visualizationmentioning
confidence: 97%
See 2 more Smart Citations
“…ET has historically been one of the most commonly used evaluation frameworks (Banerjee, Murthy, & Iyer, 2015;Velázquez-Iturbide et al, 2017). Even though previous studies measured the effect of engagement level on learning outcomes, their results were not consistent (Banerjee et al, 2015).…”
Section: The Role Of Engagement With Software Visualizationmentioning
confidence: 97%
“…The evidence suggests that student engagement is an important factor for designing and building an effective and successful SV tool (Isohanni & Järvinen, 2014;Naps et al, 2003;Sorva et al, 2013;Urquiza-Fuentes & Velázquez-Iturbide, 2013;Velázquez-Iturbide, Hernán-Losada, & Paredes-Velasco, 2017). However, there is still a need for exploring the role of engagement with SV (Sirkiä & Sorva, 2015;Sorva et al, 2013).…”
Section: The Role Of Engagement With Software Visualizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Constructivism Previous studies have observed the lack of discussion about the theoretical framework that lies behind the design and development of PV (14)(15)(16). The lack of theory and framework in the development of artefacts has long been argued in the literature on CER and educational technology (17,18).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Thus, the conversion of more complex programs into others that are more accessible and less intimidating is possible. The use of 2D visualizations has a positive effect on the learning process, from an increase in the motivation [12] and participation of the students in the class [13] to the comprehension of programming concepts [14]. Alternatively, the use of 3D graphic representations provides multiple benefits to the user, from the use of three-dimensional spaces to take advantage of spatial memory capacities, in order to understand and help to remember the structure of the programs [15], to visualizing a bigger amount of program information [16], among other possibilities.…”
Section: Introductionmentioning
confidence: 99%